Hypogastric artery ligation in laparoscopic hysterectomy: results from a randomized controlled trial - Kadir Bakay; Ali Yavuzcan; Üzeyir Kalkan; Ibrahim Yalcin; Şafak Hatırnaz; Alper Başbuğ; Davut Güven (IMR Press, 2021)
Background: Concerning total laparoscopic hysterectomy (TLH), opening the retroperitoneum and prophylactic ligation of both uterine arteries (UA) is not a routine procedure during a simple hysterectomy and it is not practiced widely in gynecology education. Methods: In this study, we tried to show the prophylactic ligation of internal iliac artery anterior division (IIAD) and provide hemostasis of UA at an anatomical plane where we considered it would be easier to perform and relatively safer, in terms of distance, regarding ureteric injury, in a prospective randomized controlled trial. Results: When this technique was used the duration of the operation got longer approximately 3 minutes (min) (57.15 ± 5.46 vs. 53.66 ± 8.96 p = 0.018 and p < 0.05), but the amount of bleeding was detected to be at a significantly lower level (73.84 ± 7.18 vs. 113.96 ± 21.5 p = 0.001 and p < 0.05). Discussion: In this method, not only we found out that it is easier to ligate IIAD compared to other surgical techniques but also allows for better control of the retroperitoneal area during the procedure therefore minimizing the risk of surgical complications such as ureter damage. Moreover, as was hypothesized, IIAD ligation dramatically reduced blood loss hence verifying its use in more complex hysterectomies and pelvic lymphadenectomy.